The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1111/j.1399-3046.2004.00158.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of non‐compliance on outcome after pediatric kidney transplantation: An analysis in racial subgroups

Abstract: Renal transplantation is the therapy of choice for children with end-stage renal disease. Despite excellent patient survival, long-term graft survival is poor, especially in the African-American (AA) population. This article addresses non-compliance as a major cause of late-term graft loss in the pediatric population. Between July 1995 and September 2002, a total of 50 pediatric kidney transplants were performed at our institution. We have analyzed data for 44 of these kidney transplants. Twelve recipients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
2
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(77 citation statements)
references
References 21 publications
2
71
2
2
Order By: Relevance
“…A recent study found that 1 month after kidney transplantation, the median pill burden was 25 pills a day, and by 1 year after transplantation, 16 pills a day [19]. Increasing pill burden is associated with decreased adherence [20,21], and lack of adherence is associated with acute rejection [22,23] and graft loss [21,[24][25][26]. While there are currently available prolonged-release tacrolimus hard capsule formulations designed for once-daily dosing, data from these formulations do not suggest that they offer improved bioavailability over tacrolimus twice-daily capsules [27][28][29].…”
Section: Overview Of the Marketmentioning
confidence: 99%
“…A recent study found that 1 month after kidney transplantation, the median pill burden was 25 pills a day, and by 1 year after transplantation, 16 pills a day [19]. Increasing pill burden is associated with decreased adherence [20,21], and lack of adherence is associated with acute rejection [22,23] and graft loss [21,[24][25][26]. While there are currently available prolonged-release tacrolimus hard capsule formulations designed for once-daily dosing, data from these formulations do not suggest that they offer improved bioavailability over tacrolimus twice-daily capsules [27][28][29].…”
Section: Overview Of the Marketmentioning
confidence: 99%
“…(3,(5)(6)(7)(8)(9)(10)(11)(34)(35)(36). Therefore, the belief that adolescents are more nonadherent compared to children should be further examined.…”
Section: Immunosuppressant Therapy Adherencementioning
confidence: 99%
“…The impact of IST nonadherence on graft outcomes among pediatric RTRs has been assessed, with studies finding IST nonadherence associated with graft failure (3,(5)(6)(7)(8)(9)(10)(11). However, the generalizability of these findings is potentially limited due to the lack of samples from multicenter trials evaluating nonadherence (3,(5)(6)(7)(8)(9)(10)(11). (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Twenty percent of late acute rejections and 16% of graft losses were attributed in part to poor compliance (2). Other literature reviews have suggested that the impact of compliance on graft loss may be even greater in children (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%